MTOR and Beclin1: Two key autophagy‐related molecules and their roles in myocardial ischemia/reperfusion injury. Issue 8 (7th January 2019) - Shi, Binhao; Ma, Mengqing; Zheng, Yitian; Pan, Yanyan; Lin, Xianhe
Abstract: Autophagy is the general term of lysosomal degradation of substances in cells, which is considered the key to maintaining the normal structure and function of the heart. It also has a correlation with several heart diseases, in particular, myocardial ischemia/reperfusion (I/R) injury. At the stage of myocardial ischemia, autophagy degrades nonfunctional cytoplasmic proteins providing the critical nutrients for the critical life activities, thereby suppressing cell apoptosis and necrosis. However, autophagy is likely to affect the heart negatively in the reperfusion stage. Mammalian target of rapamycin (mTOR) and Beclin1 are two vital autophagy‐related molecules in myocardial I/R injury playing significant roles in different stages. In the ischemia stage, mTOR plays its roles through AMPK/mTOR and phosphoinositide 3‐kinase/Akt/mTOR pathway, whereas Beclin1 plays its roles through its upregulation in the reperfusion stage. A possible interaction between mTOR and Beclin1 has been reported recently, and further studies need to be done to find the underlying interaction between the two molecules in myocardial I/R injury Abstract : "Mammalian target of rapamycin (mTOR) and Beclin1 are two key autophagy‐related molecules in myocardial ischemia/reperfusion injury. In the ischemia stage, mTOR plays its roles through AMPK/mTOR and phosphoinositide 3‐kinase/Akt/mTOR pathway, whereas Beclin1 plays its roles through its upregulation in the reperfusion stage. A possible interaction between mTOR and Beclin1 may also exist."